Customer Priorities in Sustainable Food Sourcing within Jakarta’s Hospitality Sector - Tutur Wicaksono; Ongky Alex Sander (STIE Pariwisata API Yogyakarta, 2025)
This study investigates consumer preferences regarding sustainable food sourcing practices in Jakarta's hospitality sector, a region undergoing significant urban transformation with an increasing focus on sustainability. Despite global trends towards sustainable sourcing, Jakarta’s hospitality sector faces challenges in adopting such practices due to local economic and logistical constraints. Utilizing the Kano Model, this research explores key sustainable food sourcing practices, such as local sourcing, certified suppliers, waste redistribution, and eco-labeling, through a survey conducted with 187 participants. The study categorizes consumer preferences into